2018
DOI: 10.1002/jcb.27023
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene inhibits amyloid‐β‐induced neuroinflammation in a microglia cell line by inactivating the NLRP3/caspase‐1 inflammasome pathway

Abstract: Neuroinflammation has been known as an important pathogenetic contributor of Alzheimer's disease (AD). Pterostilbene is a natural compound which has neuroprotective activity. However, the effect of pterostilbene on amyloid-β (Aβ)-induced neuroinflammation has not been clarified. The aim of the present study was to investigate the effect of pterostilbene on Aβ-induced neuroinflammation in microglia. The results indicated that pterostilbene attenuated Aβ -induced cytotoxicity of BV-2 cells. Aβ induced NO product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 25 publications
5
43
0
Order By: Relevance
“…Recently, accumulating evidences have demonstrated the benefits of PTE and other analogue stilbenoids, including resveratrol, piceatannol, and gnetol, against inflammatory and oxidative processes in vitro and in vivo [ 9 ]. The anti-inflammatory effects of PTE involve many intra- and extracellular signals, including nitric oxide (NO), inducible nitric oxide synthase (iNOS), NLRP3, NF- κ B, TNF- α , and ILs [ 26 28 , 42 , 43 ]. We previously reported that PTE alleviates early inflammatory injury after SAH by inhibiting NLRP3 inflammasome and Nox2-related oxidative stress [ 24 ] and also attenuates the secondary astrocyte-induced inflammatory and oxidative stress after ischemia reperfusion injury by suppressing NF- κ B signalling [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, accumulating evidences have demonstrated the benefits of PTE and other analogue stilbenoids, including resveratrol, piceatannol, and gnetol, against inflammatory and oxidative processes in vitro and in vivo [ 9 ]. The anti-inflammatory effects of PTE involve many intra- and extracellular signals, including nitric oxide (NO), inducible nitric oxide synthase (iNOS), NLRP3, NF- κ B, TNF- α , and ILs [ 26 28 , 42 , 43 ]. We previously reported that PTE alleviates early inflammatory injury after SAH by inhibiting NLRP3 inflammasome and Nox2-related oxidative stress [ 24 ] and also attenuates the secondary astrocyte-induced inflammatory and oxidative stress after ischemia reperfusion injury by suppressing NF- κ B signalling [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have found that PTE attenuates neural impairments in different neurological disorders, including glutamate or high-glucose-induced oxidative stress in neural cells [ 19 , 20 ], inflammation and mitochondrial oxidative stress injury after cerebral ischemia reperfusion [ 18 , 25 ], inflammation and oxidation-involved early brain injury following subarachnoid haemorrhage (SAH) [ 24 ]. Additionally, recent studies have shown that PTE inhibits the amyloid- β - and lipopolysaccharide- (LPS-) induced activation of microglia [ 26 28 ], whereas, it remains not fully clear whether PTE exerts neuronal protective effects by regulating microglia-mediated inflammatory and oxidative injury, as well as the molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that pterostilbene exhibited higher oral availability than that from resveratrol due to its two methoxy groups . In the BV2 microglia cells, pterostilbene increased cell viability and alleviated inflammation through suppressing expression of proinflammatory cytokines, NLRP3 and caspase‐1 . Treatment with z‐YVAD‐fmk as a caspase‐1 inhibitor has confirmed that pterostilbene alleviated neuroinflammation in BV‐2 microglial cells due, at least in part, to regulation of the NLRP3/caspase‐l/IL‐1β axis.…”
Section: Health Promoting Potentials Of Dietary Phytochemicalsmentioning
confidence: 92%
“…In a model of Aβ (Aβ1-42)-induced neuroinflammation in BV-2 murine microglial cells, pterostilbene decreases the expression and levels of NO and proinflammatory cytokines (IL-6, IL-1β, and TNF-α). Furthermore, pterostilbene was able to inhibit the inflammasome NLRP3/caspase-1 (CASP1) pathway, being a promising agent for the treatment of AD (Li et al, 2018). Pterostilbene was more effective than RV in neuromodulating the deleterious effects of aging and AD.…”
Section: Methoxylated Resveratrol Derivativesmentioning
confidence: 99%